Dairy replacement heifer nutrition - Morrill, J.L. (Kansas Agricultural Experiment Station, 2012)
Proper nutrition and management are necessary to provide adequate numbers of healthy herd replacements. Satisfactory heifer programs must take into consideration care of the dam and characteristics of the newborn calf, including the deficiency of circulating antibodies at birth and the lack of a functioning rumen. Nutrition. Nutrition of the dry cow is very important because of the effect this has on the next lactation as well as 0[1 the developing fetus. Several points should receive special attention. (l) Provide adequate protein and energy to meet requirements. (2) Increase concentrate intake gradually during the last part of the • dry period, so that rumen microorganisms will be adapted to the ration to be fed • ,. after freshening. Do not allow cows to get too fat. (3) Be sure intake and balance of minerals are correct. A calcium-phosphorus ratio of about 1.4:1 is recommended. Housing. By nature, the cow attempts to isolate herself from other animals to deliver her calf, and this practice helps prevent contamination of the newborn calf with infectious agents. With increased confinement, this is not possible, and special precautions should be taken to provide a clean environment for the calf during and following calving, when it is highly susceptible to diseases. A clean, well bedded, well ventilated stall should be provided in a location where the cow can be observed frequently with a minimum amount of disturbance. Other. The udder of the cow should be cleaned before the calf nurses. It is especially important that bacteria do not gain entrance to the intestines before absorption of colostrum takes place.
Keywords: Dairy; Heifer; Nutrition; Housing; Colostrum